Safety awareness among user in escalator utilization at commercial building in Cheras, Selangor / Nurul Atiqah Ahmed - Ahmed, Nurul Atiqah (2021)
This study is to show the awareness level of the local community in Cheras, Selangor on the topic of safety among escalator user. This is because the escalator is very crucial to transport a person from one place to another. Despite that, there are many cases recorded the accidents in relation to escalator. There may occur due lack of awareness among users, poor safety practice, negligence and others. Also, this research was aim to determine the escalator user and safety practices in commercial building. In addition, for this research, the method to obtain data from the public community is only through online questionnaire due to the sudden outbreak of COVID-19 in Malaysia.